Seasonal influence on structuring aquatic insects communities in upstream rivers Belum-Temengor Forest Complex - Dhiya Shafiqah Ridzuan,; Che Salmah Md Rawi,; Suhaila Ab Hamid, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
The plausible effect of seasonal change (wet and dry) on the structure of aquatic insect community was investigated at rivers in Belum-Temengor Forest Complex (BTFC), Perak, Malaysia. The amount of rainfall received was considered as seasonal changes in the tropical regions. The rivers were visited twice in dry and wet seasons to sample aquatic insects using rectangular aquatic nets. Their abundance and richness varied significantly between both dry and wet seasons (P = 0.000; Mann-Whitney U test). More aquatic insect was collected in dry seasons (17,633 individuals) compared to wet seasons (6,542 individuals). The aquatic insect abundance decreased tremendously during the wet seasons (45% reduction) and diversity showed fewer species richness in the wet season (98 genera) compared to the dry season (114 genera). The most affected taxa caused by the heavy water flow were Ceratopsyche sp. (family Hydropschidae and subfamily Limoniinae which huge reduction in density occurred during the wet season. Water temperature, BOD3, DO and COD were significantly different between seasons (Kruskal Wallis test, P < 0.05). The presence of phosphorus and ammonia-nitrogen in water during dry season had major influence on the aquatic insect composition while rainfall was the main factor that regulated the insect communities in wet seasons.